2017
DOI: 10.1371/journal.pone.0189768
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial to evaluate the effect of fecal microbiota transplant for initial Clostridium difficile infection in intestinal microbiome

Abstract: ObjectiveThe aim of this study was to evaluate the impact of fecal donor-unrelated donor mix (FMT-FURM) transplantation as first-line therapy for C. difficile infection (CDI) in intestinal microbiome.MethodsWe designed an open, two-arm pilot study with oral vancomycin (250mg every 6 h for 10–14 days) or FMT-FURM as treatments for the first CDI episode in hospitalized adult patients in Hospital Universitario “Dr. Jose Eleuterio Gonzalez”. Patients were randomized by a closed envelope method in a 1: 1 ratio to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 29 publications
1
52
0
Order By: Relevance
“…The inconsistency in the results of the four included studies may be attributed to their small sample sizes, lack of blinding and variability between them on the basis of the process of collecting donor faeces, preparation of FMT, lag time between faeces collection and infusion, method of administration and SAT regimen. Furthermore, as evident from the findings of a previous RCT, patients who received FMT monotherapy for an initial episode of CDI without receiving prior antibiotics, retained more bacteroidetes in their gut than patients treated with antibiotics 22. These findings confirm the effect of antibiotics in attenuating intrinsic microbiota 5.…”
Section: Discussionsupporting
confidence: 57%
“…The inconsistency in the results of the four included studies may be attributed to their small sample sizes, lack of blinding and variability between them on the basis of the process of collecting donor faeces, preparation of FMT, lag time between faeces collection and infusion, method of administration and SAT regimen. Furthermore, as evident from the findings of a previous RCT, patients who received FMT monotherapy for an initial episode of CDI without receiving prior antibiotics, retained more bacteroidetes in their gut than patients treated with antibiotics 22. These findings confirm the effect of antibiotics in attenuating intrinsic microbiota 5.…”
Section: Discussionsupporting
confidence: 57%
“…Antibiotics are efficacious in the treatment of CDI93–95 and considered first-line therapy for an initial episode of CDI 96 97. FMT has been used in first-episode CDI and has comparable efficacy with antibiotics 98–100. Further research is required to assess the clinical efficacy of FMT in this setting.…”
Section: Resultsmentioning
confidence: 99%
“…However, 37.5% (n=6/16) of the patients treated with FMT within a week of CDI diagnosis required further antibiotics and a second FMT within 1 month of the first FMT because of relapse 61. In a small pilot randomised trial, patients were randomised to either vancomycin or multi-donor FMT (administered either via upper or lower GI routes) as initial therapy for CDI; CDI resolution occurred in 88.9% (n=8/9) of patients with vancomycin, compared with 57.1% of patients (n=4/7) with one FMT, and 71.4% of patients (n=5/7) after two FMTs 62. Given the small size of these studies and equivocal results, the working group concluded that the reviewed studies did not support FMT as initial therapy for CDI.…”
Section: Rationale For Recommendationsmentioning
confidence: 99%